Modelling Australian land use competition and ecosystem services with food price feedbacks at high spatial resolution. (July 2015) - Connor, Jeffery D.; Bryan, Brett A.; Nolan, Martin; Stock, Florian; Gao, Lei; Dunstall, Simon; Graham, Paul; Ernst, Andreas; Newth, David; Grundy, Mike; Hatfield-Dodds, Steve
Abstract: In a globalised world, land use change outlooks are influenced by both locally heterogeneous land attributes and world markets. We demonstrate the importance of high resolution land heterogeneity representation in understanding local impacts of future global scenarios with carbon markets and land competition influencing food prices. A methodologically unique Australian continental model is presented with bottom-up parcel scale granularity in land use change, food, carbon, water, and biodiversity ecosystem service supply determination, and partial equilibrium food price impacts of land competition. We show that food price feedbacks produce modest aggregate national land use and ecosystem service supply changes. However, high resolution results show amplified land use change and ecosystem service impact in some places and muted impacts in other areas relative to national averages. We conclude that fine granularity modelling of geographic diversity produces local land use change and ecosystem service impact insights not discernible with other approaches. Highlights: We modeled Australian land use change and ecosystem service responses to global scenarios. The model features a novel approach to very high resolution land heterogeneity representation. To demonstrate, we model how food price feedbacks of land competition differ spatially. Modest land use change and ecosystem service impacts are observed in aggregate for Australia. High resolution impacts vary from large to minuscule depending on local land heterogeneity.